Clinical significance of changes in the expression level of markers of surrogate breast cancer subtypes in recurrent and metastatic foci (literature review) - Yu. S. Krumin; V. A. Khaylenko; N. A. Kozlov; G. Yu. Cheremis; A. V. Petrovskyy; D. V. Khaylenko; E. V. Artamonova; E. I. Kovalenko (ABV-press, 2021)
The article analyzes data from the world literature for the period from 2005 to 2020 on the relationship between the variability of immunohistochemical expression of estrogen and progesterone receptors, HER2/neu protein and the index of proliferative activity in invasive breast cancer with the course of the disease and the response to medication.